An asymptomatic young lady with multiple inflammatory myofibrolastic tumours - How, Soon Hin; Ralib, Razali; AR, Azlina; Kuan, Yeh Chunn; Ng, Teck Han; Abdul Rani, Mohammed Fauzi (OMICS Publishing Group, 2012)
Introduction: We report a case of inflammatory myofibroblastic tumour with positive PET-CT involving the lung, hilar lymph node, liver and spleen in an asymptomatic young girl. Diagnosis was made four years after the initial presentation. Treatment: Conservative treatment. Outcome: Patient remained asymptomatic for 4 years. Conclusions: Multiple inflammatory myofibroblastic tumour may remain asymptomatic despite multiple organs involvement.